Adjusting Interfacial Chemistry and Electronic Properties of Photovoltaics Based on a Highly Pure Sb2S3 Absorber by Atomic Layer Deposition - Büttner, Pascal; Scheler, Florian; Pointer, Craig; Döhler, Dirk; Barr, Maissa; Koroleva, Aleksandra; Pankin, Dmitrii; Hatada, Ruriko; Flege, Stefan; Manshina, Alina; Young, Elizabeth R.; Minguez Bacho, Ignacio; et al. (ACS Applied Energy Materials, 2019)
The combination of oxide and heavier chalcogenide layers in thin film photovoltaics suffers limitations associated with oxygen incorporation and sulfur deficiency in the chalcogenide layer or with a chemical incompatibility which results in dewetting issues and defect states at the interface. Here, we establish atomic layer deposition (ALD) as a tool to overcome these limitations. ALD allows one to obtain highly pure Sb2S3 light absorber layers, and we exploit this technique to generate an additional interfacial layer consisting of 1.5 nm ZnS. This ultrathin layer simultaneously resolves dewetting and passivates defect states at the interface. We demonstrate via transient absorption spectroscopy that interfacial electron recombination is one order of magnitude slower at the ZnS-engineered interface than hole recombination at the Sb2S3/P3HT interface. The comparison of solar cells with and without oxide incorporation in Sb2S3, with and without the ultrathin ZnS interlayer, and with systematically varied Sb2S3 thickness provides a complete picture of the physical processes at work in the devices.
CRIS-Team Scopus Importer:2019-12-27
Keywords: antimony sulfide; atomic layer deposition; extremely thin absorber; interfacial layer; transient absorption; ultrathin layer

A Geometrically Well-Defined and Systematically Tunable Experimental Model to Transition from Planar to Mesoporous Perovskite Solar Cells - Döhler, Dirk; Büttner, Pascal; Scheler, Florian; Thiel, Dominik; Puscher, Bianka; Bochmann, Sebastian; Mitrovic, Julian; Boix, Pablo P.; Guldi, Dirk Michael; Minguez-Bacho, Ignacio; Bachmann, Julien (ACS Applied Energy Materials, 2022)
A series of perovskite solar cells with systematically varying surface area of the interface between n-type electron conducting layer (TiO2) and perovskite are prepared by using an ordered array of straight, cylindrical nanopores generated by anodizing an aluminum layer evaporated onto a transparent conducting electrode. A series of samples with pore length varied from 100 to 500 nm are compared to each other and complemented by a classical planar cell and a mesoporous counterpart. All samples are characterized in terms of morphology, chemistry, optical properties, and performance. All samples absorb light to the same degree, and the increased interface area does not generate enhanced recombination. However, the short circuit current density increases monotonically with the specific surface area, indicating improved charge extraction efficiency. The importance of the slow interfacial rearrangement of ions associated with planar perovskite cells is shown to decrease in a systematic manner as the interfacial surface area increases. The results demonstrate that planar and mesoporous cells obey to the same physical principles and differ from each other quantitatively, not qualitatively. Additionally, the study shows that a significantly lower TiO2 surface area compared to mesoporous TiO(2 )is needed for an equal charge extraction.
CRIS-Team WoS Importer:2022-10-14

A Self‐Ordered Nanostructured Transparent Electrode of High Structural Quality and Corresponding Functional Performance - Döhler, Dirk; Triana Merlo, Andres Dario; Büttner, Pascal; Scheler, Florian; Görlitzer, Eric; Harrer, Johannes; Vasileva, Anna A.; Ali, Ezzeldin; Gruber, Wolfgang; Unruh, Tobias; Manshina, Alina A.; Vogel, Nicolas; et al. (Small, 2021)
The preparation of a highly ordered nanostructured transparent electrode based on a combination of nanosphere lithography and anodization is presented. The size of perfectly ordered pore domains is improved by an order of magnitude with respect to the state of the art. The concomitantly reduced density of defect pores increases the fraction of pores that are in good electrical contact with the underlying transparent conductive substrate. This improvement in structural quality translates directly and linearly into an improved performance of energy conversion devices built from such electrodes in a linear manne
Keywords: nanosphere lithography; anodic alumina; antimony sulfide

A solution-based ALD route towards (CH3NH3)(PbI3) perovskite via lead sulfide films - Koch, Vanessa; Barr, Maissa; Büttner, Pascal; Mínguez-Bacho, Ignacio; Döhler, Dirk; Winzer, Bettina; Reinhardt, Elisabeth; Segets, Doris; Bachmann, Julien (Journal of Materials Chemistry A, 2019)
We present a procedure to grow thin films of lead sulfide (PbS) with 'solution Atomic Layer Deposition' (sALD), a technique which transfers the principles of ALD from the gas phase (gALD) to liquid processing. PbS thin films are successfully deposited on planar and porous substrates with a procedure that exhibits the unique ALD characteristics of self-limiting surface chemistry and linear growth at room temperature. The polycrystalline p-type PbS films are stoichiometric and pure. They are converted to the hybrid perovskite methylammonium iodoplumbate (methylammonium lead iodide, MAPI, CH3NH3PbI3) by annealing to 150 °C in the presence of vapors from methylammonium iodide (MAI).
CRIS-Team Scopus Importer:2019-11-19

Continuous, crystalline Sb2S3 ultrathin light absorber coatings in solar cells based on photonic concentric p-i-n heterojunctions - Büttner, Pascal; Scheler, Florian; Döhler, Dirk; Barr, Maissa; Bosch, Michael; Rey, Marcel; Yokosawa, Tadahiro; Hinz, Sandra; Maultzsch, Janina; Spiecker, Erdmann; Vogel, Nicolas; Minguez Bacho, Ignacio; et al. (Nano Energy, 2022)
Many modern types of solar cells that rely exclusively on earth-abundant non-toxic materials include interfaces between a heavier metal chalcogenide and another type of semiconductor. Often, the chemical (adhesion) and physical (charge transfer) characteristics of those interfaces are the defining factors for the final device performance. Here, we describe that a ZnS adhesion layer is not sufficient to prevent the dewetting of Sb2S3 upon annealing a thin layer of it on an oxidic surface if the substrate is not planar and features highly curved surfaces. An ALD-coated sacrificial capping layer of ZnO prevents the morphological rearrangements of Sb2S3 during thermal crystallization and can be removed subsequently. When implemented towards a photovoltaic p-i-n heterojunction, this strategy furnishes perfect conformality of the layer stack but unsatisfactory performance. The correlation of interface chemistry with the electrical properties and the device performance identifies a reducing effect of ZnO atomic layer deposition chemistry on the Sb2S3 surface as the cause of Zn diffusion into the light absorbing semiconductor. This deleterious doping can be prevented by a preliminary oxidative treatment of the Sb2S3 surface with ozone. When applied to a structured substrate consisting of ordered arrays of nanospheres, this approach yields the first ever concentric p-i-n heterojunction solar cells with photonic light trapping effect—a geometry which in comparison with standard scattering layers'on top’ inherently generates a very large refractive index contrast. In the red part of the visible spectrum, light absorption amounts to the value expected with four passes through a planar layer of the thickness used here (35 nm Sb2S3). This effect allows us to demonstrate >5% overall solar energy conversion efficiency with only 35 nm of a simple light absorber phase that uses no toxic, rare materials
CRIS-Team Scopus Importer:2022-10-14
Keywords: Atomic layer deposition; Concentric semiconductor junctions; Antimony chalcogenides; Interfacial layers; Photonic structures; Gradient doping; Interface chemistry

Elucidating Mechanistic Details of Photo-Induced Charge Transfer in Antimony Sulfide-Based p-i-n Junctions - Pointer, Craig; Büttner, Pascal; Scheler, Florian; Döhler, Dirk; Minguez-Bacho, Ignacio; Bachmann, Julien; Young, Elizabeth R. (Journal of Physical Chemistry C, 2021)
The initial kinetics and mechanisms of photo-induced charge transfer in photovoltaic materials are critical to the operation of fabricated devices. Despite the importance of charge transfer in the picosecond to nanosecond timescales, mechanistic understanding of these events is still limited. To address this challenge, a series of p-i-n junction samples that comprises fluorine-doped tin oxide (FTO)/TiO2/ZnS/Sb2S3/P3HT layers was prepared by atomic layer deposition (ALD). ALD allows for carefully controlled film thickness in samples that enable systematic evaluation of photo-induced charge-transfer kinetics by transient absorption spectroscopy (TAS). Sb2S3 serves as the intrinsic light absorber, P3HT is the hole acceptor, and TiO2 is the electron acceptor. An extremely thin, electron-blocking layer of ZnS was deposited between Sb2S3 and TiO2 varied in thickness by ALD to create a series of 20 samples that included (1) five different ZnS thicknesses (0, 2, 5, 10, and 15 ALD cycles) and (2) four combinations of layers, always including ZnS/Sb2S3, that built up to the completed stack. These mechanistic studies confirm our proposed mechanism for photo-induced electron and hole transfer and recombination in these p-i-n junction samples and provide predictive insights into the charge-transfer processes that may be most determinant in the operation of completed devices.
CRIS-Team Scopus Importer:2021-09-10

Highly Active Ir/TiO2 Electrodes for the Oxygen Evolution Reaction Using Atomic Layer Deposition on Ordered Porous Substrates - Schlicht, Stefanie; Büttner, Pascal; Bachmann, Julien (ACS Applied Energy Materials, 2019)
Nanostructured Ir/TiO2 electrodes are investigated toward the oxygen evolution reaction (OER) from water. The electrodes are prepared based on highly ordered TiO2 nanotubes grown from Ti foils with full geometric control. The tube walls are coated with iridium using atomic layer deposition (ALD), which allows for an accurate tuning of the amount deposited. The electrocatalytic performance of electrodes with different TiO2 tube lengths and iridium catalyst loadings toward OER is quantified by cyclic voltammetry and steady-state electrolysis. This study enables us to minimize the catalyst loading, and we reach a current density of 31.3 mA cm(-2) at an overpotential eta = 0.34 V for a tube length of L = 12 mu m and a Ir coating thickness of t = 6 nm. The benchmark of 10 mA cm(-2) is already achieved at a lower overpotential of eta = 0.24 V.
CRIS-Team WoS Importer:2019-04-12

Monolithic Two-Terminal Tandem Solar Cells Using Sb2S3 and Solution-Processed PbS Quantum Dots Achieving an Open-Circuit Potential beyond 1.1 V - Kern, Selina; Yi, Gyusang; Büttner, Pascal; Scheler, Florian; Tran, Minh Hoa; Korenko, Sofia; Dehm, Katharina; Kundrata, Ivan; Zahl, Achim; Albrecht, Steve; Bachmann, Julien; Crisp, Ryan (ACS Applied Materials and Interfaces, 2024)
Multijunction solar cells have the prospect of a greater theoretical efficiency limit than single-junction solar cells by minimizing the transmissive and thermalization losses a single absorber material has. In solar cell applications, Sb2S3 is considered an attractive absorber due to its elemental abundance, stability, and high absorption coefficient in the visible range of the solar spectrum, yet with a band gap of 1.7 eV, it is transmissive for near-IR and IR photons. Using it as the top cell (the cell where light is first incident) in a two-terminal tandem architecture in combination with a bottom cell (the cell where light arrives second) of PbS quantum dots (QDs), which have an adjustable band gap suitable for absorbing longer wavelengths, is a promising approach to harvest the solar spectrum more effectively. In this work, these two subcells are monolithically fabricated and connected in series by a poly(3,4-ethylene-dioxythiophene) polystyrene sulfonate (PEDOT:PSS)-ZnO tunnel junction as the recombination layer. We explore the surface morphology of ZnO QD films with different spin-coating conditions, which serve as the PbS QD cell’s electron transport material. Furthermore, we examine the differences in photogenerated current upon varying the PbS QD absorber layer thickness and the electrical and optical characteristics of the tandem with respect to the stand-alone reference cells. This tandem architecture demonstrates an extended spectral response into the IR with an open-circuit potential exceeding 1.1 V and a power conversion efficiency of 5.6%, which is greater than that of each single-junction cell.
CRIS-Team Scopus Importer:2024-03-29
Keywords: antimony sulfide; atomic layer deposition; chalcogenide solar cells; lead sulfide; mapping ellipsometry; multijunction; nanocrystals; recombination layer

Ordered nanopore arrays with large interpore distances via one-step anodization - Minguez Bacho, Ignacio; Scheler, Florian; Büttner, Pascal; Bley, Karina; Vogel, Nicolas; Bachmann, Julien (Nanoscale, 2018)
Preparation of pre-patterned alumina substrates using bottom-up techniques compatible with nanotechnology applications is still a challenge. We present a novel methodology to achieve superior order in 'anodic' alumina with large interpore distances by a convenient one-step anodization process. The use of transparent insulators renders such anodic layers applicable as templates for nanostructured photovoltaic or photoelectrochemical devices.

Solid state interdigitated Sb(2)S(3)based TiO(2)nanotube solar cells - Büttner, Pascal; Döhler, Dirk; Korenko, Sofia; Möhrlein, Sebastian; Bochmann, Sebastian; Vogel, Nicolas; Minguez Bacho, Ignacio; Bachmann, Julien (RSC Advances, 2020)
TiO(2)nanotubes generated by anodization of metallic titanium sputter-coated on indium tin oxide (ITO) substrates are used as a conductive scaffold for all solid-state Sb2S3-sensitized extremely thin absorber (ETA) solar cells. A blocking layer of TiO(2)placed between Ti and ITO in combination with optimized Ti deposition and anodization conditions enables the formation of crack-free layers of straight, cylindrical TiO(2)nanotubes of tunable length and diameter. ALD (atomic layer deposition) is subsequently used to coat this substrate conformally with a highly pure Sb(2)S(3)light absorber layer under an inert atmosphere. The high absorption coefficient of Sb(2)S(3)as compared to molecular dyes allows for the utilization of very short nanotubes, which facilitates the infiltration of the organic hole transport material and formation of a p-i-n heterojunction in an interdigitated and tunable geometry. We investigate the influence of nanotube length and of the absorber thickness to enhance the photocurrent value to twice that of planar reference structures.

Solid state interdigitated Sb(2)S(3)based TiO(2)nanotube solar cells - Büttner, Pascal; Döhler, Dirk; Korenko, Sofia; Moehrlein, Sebastian; Bochmann, Sebastian; Vogel, Nicolas; Minguez-Bacho, Ignacio; Bachmann, Julien (RSC Advances, 2020)
TiO(2)nanotubes generated by anodization of metallic titanium sputter-coated on indium tin oxide (ITO) substrates are used as a conductive scaffold for all solid-state Sb2S3-sensitized extremely thin absorber (ETA) solar cells. A blocking layer of TiO(2)placed between Ti and ITO in combination with optimized Ti deposition and anodization conditions enables the formation of crack-free layers of straight, cylindrical TiO(2)nanotubes of tunable length and diameter. ALD (atomic layer deposition) is subsequently used to coat this substrate conformally with a highly pure Sb(2)S(3)light absorber layer under an inert atmosphere. The high absorption coefficient of Sb(2)S(3)as compared to molecular dyes allows for the utilization of very short nanotubes, which facilitates the infiltration of the organic hole transport material and formation of a p-i-n heterojunction in an interdigitated and tunable geometry. We investigate the influence of nanotube length and of the absorber thickness to enhance the photocurrent value to twice that of planar reference structures.
CRIS-Team WoS Importer:2020-08-28

Stability of Bimetallic PtxRuy - From Model Surfaces to Nanoparticulate Electrocatalysts - Kormanyos, Attila; Büttner, Pascal; Bosch, Michael; Minichova, Maria; Körner, Andreas; Jenewein, Ken J.; Hutzler, Andreas; Mayrhofer, Karl J.J.; Bachmann, Julien; Cherevko, Serhiy (ACS Materials Au, 2024)
Fundamental research campaigns in electrocatalysis often involve the use of model systems, such as single crystals or magnetron-sputtered thin films (single metals or metal alloys). The downsides of these approaches are that oftentimes only a limited number of compositions are picked and tested (guided by chemical intuition) and that the validity of trends is not verified under operating conditions typically present in real devices. These together can lead to deficient conclusions, hampering the direct application of newly discovered systems in real devices. In this contribution, the stability of magnetron-sputtered bimetallic PtxRuy thin film electrocatalysts (0 at. % to 100 at. % Ru content) along with three commercially available carbon-supported counterparts (50-67 at. % Ru content) was mapped under electrocatalytic conditions in acidic electrolytes using online ICP-MS. We found several differences between the two systems in the amount of metals dissolved along with the development of the morphology and composition. While the Pt-rich PtxRuy compositions remained unchanged, 30-50 nm diameter surface pits were detected in the case of the Ru-rich sputtered thin films. Contrastingly, the surface of the carbon-supported NPs enriched in Pt accompanied by the leaching of a significant amount of Ru from the alloy structure was observed. Change in morphology was accompanied by a mass loss reaching around 1-2 wt % in the case of the sputtered samples and almost 10 wt % for the NPs. Since PtxRuy has prime importance in driving alcohol oxidation reactions, the stability of all investigated alloys was screened in the presence of isopropanol. While Pt dissolution was marginally affected by the presence of isopropanol, several times higher Ru dissolution was detected, especially in the case of the Ru-rich compositions. Our results underline that trends in terms of electrocatalytic activity and stability cannot always be transferred from model samples to systems that are closer to the ones applied in real devices.
CRIS-Team Scopus Importer:2024-05-24
Keywords: bimetallic electrocatalyst; dealloying; electrocatalyst stability; material library; online ICP-MS

ZnS Ultrathin Interfacial Layers for Optimizing Carrier Management in Sb2S3-based Photovoltaics - Büttner, Pascal; Scheler, Florian; Pointer, Craig; Döhler, Dirk; Yokosawa, Tadahiro; Spiecker, Erdmann; P. Boix, Pablo; Young, Elizabeth R.; Minguez Bacho, Ignacio; Bachmann, Julien (ACS Applied Materials and Interfaces, 2021)
Antimony chalcogenides represent a family of materials of low toxicity and relative abundance, with a high potential for future sustainable solar energy conversion technology. However, solar cells based on antimony chalcogenides present open-circuit voltage losses that limit their efficiencies. These losses are attributed to several recombination mechanisms, with interfacial recombination being considered as one of the dominant processes. In this work, we exploit atomic layer deposition (ALD) to grow a series of ultrathin ZnS interfacial layers at the TiO2/Sb2S3 interface to mitigate interfacial recombination and to increase the carrier lifetime. ALD allows for very accurate control over the ZnS interlayer thickness on the ångström scale (0–1.5 nm) and to deposit highly pure Sb2S3. Our systematic study of the photovoltaic and optoelectronic properties of these devices by impedance spectroscopy and transient absorption concludes that the optimum ZnS interlayer thickness of 1.0 nm achieves the best balance between the beneficial effect of an increased recombination resistance at the interface and the deleterious barrier behavior of the wide-bandgap semiconductor ZnS. This optimization allows us to reach an overall power conversion efficiency of 5.09% in planar configuratio
Keywords: tunnel barrier; interfacial layer; passivation layer; anti-recombination layer; chalcogenides; extremely thin absorber; thin film solar cells; atomic layer deposition